A dual‐band dual‐sense circularly polarized self‐diplexing SIW cavity‐backed antenna with elliptical slot for millimeter‐wave 5G applications. Issue 10 (28th June 2022) - Kumar, Amit; Kumar, Munish; Singh, Amit Kumar
Abstract: In this paper, a substrate integrated waveguide (SIW)‐based circularly polarized (CP) self‐diplexing antenna is proposed and discussed. The proposed antenna makes use of an elliptical slot in the metallic ground plane which is excited with the help of two separate microstrip feed lines, placed face‐to‐face with each other. This arrangement produces two different frequencies, centered around 21.70 and 27.10 GHz when separately excited by port‐1 and port‐2, respectively. The CP operation in both frequency bands can be brought by rotating the elliptical slot, which gives 3 dB axial‐ratio bandwidth (ARBW) of 3.01% and 6.62% in lower and upper‐frequency bands, respectively. A unidirectional radiation pattern and a peak gain of 7.70 and 9.84 dBic are obtained in lower and upper‐frequency bands, respectively. The radiation efficiency of more than 80% in both the operating frequency bands has been achieved. The behavior of the cavity modes is explained using an equivalent circuit model. The proposed antenna has been fabricated and the measured results are experimentally verified with the simulated ones. The attractive features such as low profile and low weight make the proposed SIW antenna suitable for satellite and millimeter‐wave 5G applications.